Pengaruh Assertif Training Therapy terhadap Kemampuan Mengelola Emosi Anak Sekolah (USIA 9-11 Tahun) di SDN Woromarto 1 - Laviana Nita L; Puput Yosie (STIKes Patria Husada Blitar, 2016)
Assertive Training Therapy represent a training technique to teach and familiarize individuals behave assertively in relationships with other people, able to control himself, feel free and fun, able to respond to love things and express love and affect people who are very meaningful in their life. The objective of this research was to know the effect of Assertive Training therapy to the ability to manage emotions of school children (age 9-11 years). The research design used Quasy Experimental with the population of 32 children with purposive sampling technique. The research instruments used observation and questionnaires with statistical test of Mann Whitney ï² < ï¡ with result 0,02 < 0,05 that means H0 rejected means there was difference between control group and intervention group, and also the existence of influence on intervention group. Based on the data indicated that most of children before conducted intervention had aggressive behavior, but after the giving of intervention of Assertive Training Therapy the children behavior changes becomes assertive. This because during the intervention children taught the way to express feeling correctly by conducted therapy of four sessions. Parents and teachers were expected to understand what the child feels in managing emotions to assist children in expressing the desire that the child feels in a way of Assertive Training Therapy that includes 4 sessions.